A Far Country $1 (BVolume 3s - Churchill, Winston, 1871-1947 (Salt Lake City, UT : Project Gutenberg, 2004)
"A Far Country $1 (BVolume 3" by Winston Churchill is a historical novel written during the early 20th century. This installment continues to explore themes of wealth, societal change, and personal relationships in a burgeoning American city, with a particular focus on the lives of the Durrett family, among others, as they navigate the complexities of wealth and moral ambivalence. The opening of this volume introduces readers to a city that has become synonymous with sudden wealth, attracting visitors from around the world. The narrative shifts to the lives of Mr. and Mrs. Hambleton Durrett, whose personal circumstances reflect the larger social trends of their time. As wealthy individuals, they embody the new cultural norms, which have significantly transformed since the days of Mr. Durrett$1 (Bs father$1 (Ba stern believer in Calvinism. The protagonist reflects on his complicated feelings about his past intimacy with Nancy while contemplating a renewed connection, even as he grapples with marital duties and societal expectations. This opening sets the stage for deeper explorations of personal longing, the strain of marriage, and the cultural tensions between progress and tradition amid a rapidly changing society. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/A_Far_Country_(novel)
Release date is 2004-10-17
Produced by Pat Castevans and David Widger
Keywords: Upper class families -- Fiction; Religion and sociology -- Fiction; Ethics -- Fiction